Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.4168/aair.2014.6.2.156
|View full text |Cite
|
Sign up to set email alerts
|

Cross-reactivity to Acetaminophen and Celecoxib According to the Type of Nonsteroidal Anti-inflammatory Drug Hypersensitivity

Abstract: PurposeIdentification of tolerable alternative analgesics is crucial for management in nonsteroidal anti-inflammatory drug (NSAID)-sensitive patients. We investigated cross-reactivity of acetaminophen and celecoxib according to the type of aspirin/NSAID hypersensitivity and aimed to determine the risk factors for cross-intolerance.MethodsWe retrospectively reviewed the medical records of patients intolerant to aspirin and NSAIDs who had undergone an acetaminophen and/or celecoxib oral provocation test. Aspirin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 23 publications
1
28
0
Order By: Relevance
“…Unlike most NSAIDs, acetaminophen administration at therapeutic doses has little or no anti-inflammatory or anti-platelet activity (29). Additionally, it does not exhibit the typical side effect profile of NSAIDs, which includes gastrointestinal tract problems and aspirininduced asthma (37,38). Although acetaminophen is among the most popular and widely used analgesics, the mechanism of its analgesic action remain uncertain, though the most suggested mechanism involves inhibition of COX activity (39).…”
Section: Discussionmentioning
confidence: 99%
“…Unlike most NSAIDs, acetaminophen administration at therapeutic doses has little or no anti-inflammatory or anti-platelet activity (29). Additionally, it does not exhibit the typical side effect profile of NSAIDs, which includes gastrointestinal tract problems and aspirininduced asthma (37,38). Although acetaminophen is among the most popular and widely used analgesics, the mechanism of its analgesic action remain uncertain, though the most suggested mechanism involves inhibition of COX activity (39).…”
Section: Discussionmentioning
confidence: 99%
“…in 63%). Therefore, like other researchers, we recommend a DPT to provide an assurance of tolerance before prescribing these drugs for patients with suspected NSAID HS [13,19,39,40]. …”
Section: Discussionmentioning
confidence: 99%
“…Reactions to acetaminophen are unusual but can occur. [28][29][30][31][32] The dogma indicates that reactions in patients with AERD are triggered by the inhibition of COX-1, which is not a biologic activity of nonaspirin salicylates and, as such, dietary salicylates are generally not thought to trigger reactions. However, results of recent research showed that a low-salicylate diet perhaps leads to a reduction in symptoms in some patients with AERD.…”
Section: Chronic Sinusitis With Npsmentioning
confidence: 99%